Strategi Pembelajaran Dosen Melalui Pemanfaatan Media Whatsapp Di Masa Pandemi COVID-19 - Jessika Tamara; Sugiatno Sugiatno; Eka Yanuarti; Idi Warsah; Deri Wanto (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
Abstract: Islamic Education Lecturers’ Learning Strategy By Making Use Of Whatsapp Media During Covid-19 PandemicThis study aimed to find out a portrayal of learning strategy undertaken by IAIN lecturers during the Covid-19 pandemic towards Islamic Education (PAI) students in semester VI of the academic year 2019/2020 by making use of Whatsapp. This study employed a qualitative approach, and the informants were PAI lecturers and PAI department students in semester VI. The data of this study were collected using observation and interviews, and then analyzed using the approach of Miles et al, namely data reduction, data presentation, and conclusion drawing. This study concluded that the portrayal of PAI lecturers’ learning strategy by making use of Whatsapp media started from a joint commitment between students and lecturers, one of which must cooperate with each other so that learning was achieved. PAI lecturers used documents attached in PDF or MCWORD format and then sent to students via Whatsapp. When the material needed to be discussed, through WA groups students could provide feedback on the material provided. If the signal was not possible to communicate, the lecturers went to a location with a better signal and a provider with a good signal with the aim that the learning process could be carried out properly even though it was done online in midst of covid-19 pandemic as it is today.Abstrak: Strategi Pembelajaran Dosen Melalui Pemanfaatan Media Whatsapp di Masa Pandemi Covid-19Penelitian ini bertujuan untuk menemukan gambaran strategi pembelajaran dosen IAIN Curup di masa pandemic Covid 19 pada mahasiswa program studi Pendidikan Agama Islam (PAI) semester VI tahun akademik 2019/2020 dengan menggunakan media Whatsapp. Penelitian ini menggunakan pendekatan kualitatif dan sebagai informan adalah dosen PAI dan mahasiswa Prodi PAI semester VI. Data dikumpulkan dengan observasi dan wawancara lalu dianalisis menggunakan pendekatan Miles et.al yakni Reduksi data, penyajian data dan penarikan kesimpulan. Simpulannya bahwa gambaran strategi pembelajaran dosen melalui pemanfaatan media whatsapp oleh dosen prodi PAI, dimulai dari komitmen bersama antara mahasiswa dan dosen salah satunya harus saling bekerja sama agar pembelajaran tercapai. Dosen prodi PAI menggunakan dokumen yang dilampirkan dalam bentuk pdf ataupun word kemudian dikirim kepada mahasiswa via whatsapp, ketika materi tersebut perlu didiskusikan, melalui grup wa mahasiswa dapat memberikan tanggapan atas materi yang diberikan. Jika sinyal tidak memungkinkan untuk berkomunikasi dosen beranjak ke lokasi dengan sinyal yang lebih baik dan provider dengan sinyal yang baik dengan tujuan agar proses pembelajaran dapat terlaksana dengan baik meskipun dilakukan secara online di tengah pandemi covid-19 seperti saat ini.